2008
DOI: 10.1590/s0006-87052008000100031
|View full text |Cite
|
Sign up to set email alerts
|

Escala fenológica detalhada da fase reprodutiva de Cooffea arabica

Abstract: RESUMONeste trabalho se propõe uma escala fenológica detalhada para identificar e caracterizar visualmente todas as fases de desenvolvimento reprodutivo do cafeeiro. O estudo foi realizado em condições de campo com a cultivar IAPAR 59, no período de maio de 2004 a maio de 2005 em Londrina, PR (23 o 23' S, 50 o 11' W, 610 m). Periodicamente, foram realizadas medições de crescimento e caracterização evolutiva da morfologia externa das gemas florais, flores e frutos dos ramos plagiotrópicos, em intervalos variado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 2 publications
1
49
0
5
Order By: Relevance
“…Segundo Morais et al (2008), a passagem da gema à fase reprodutiva pode ser caracterizada pelos seguintes estádios ou subfases: G1 -nós com gemas indiferenciadas; G2 -nós com gemas intumescidas; G3 -gemas com até 3,0 mm de comprimento; G4 -gemas medindo de 3,1 mm a 6,0 mm de comprimento; G5 -gemas de 6,1 mm a 10,0 mm (coloração verde clara); e G6 -gemas maiores que 10,0 mm (coloração branca). Após o G6, normalmente, ocorre abertura das flores nas primeiras horas da manhã, as quais começam a murchar, no segundo dia, caindo no terceiro.…”
Section: Fisiologia Do Estresse Hídrico Em Caféunclassified
“…Segundo Morais et al (2008), a passagem da gema à fase reprodutiva pode ser caracterizada pelos seguintes estádios ou subfases: G1 -nós com gemas indiferenciadas; G2 -nós com gemas intumescidas; G3 -gemas com até 3,0 mm de comprimento; G4 -gemas medindo de 3,1 mm a 6,0 mm de comprimento; G5 -gemas de 6,1 mm a 10,0 mm (coloração verde clara); e G6 -gemas maiores que 10,0 mm (coloração branca). Após o G6, normalmente, ocorre abertura das flores nas primeiras horas da manhã, as quais começam a murchar, no segundo dia, caindo no terceiro.…”
Section: Fisiologia Do Estresse Hídrico Em Caféunclassified
“…As a result, to sustain a high load of fruits in wider spacing, with low RAFFr, the individual mass of sinks (mass/fruit) was lowered. In December 2013, fruits had not yet entered the phase of high carbohydrate demand, which only occurred later in the fruit-filling phase (MORAIS et al, 2008;DaMATTA et al, 2007;LAVIOLA et al, 2007). In fact, in the assessment performed in April 2014, unlike that made in the previous year, the spacing factor alone did not affect variables related to plagiotropic branches, such that the RAFFr remained at approximately 19 cm 2 fruit -1 , regardless of factors investigated.…”
Section: Resultsmentioning
confidence: 86%
“…According to Pezzopane et al (2003) and Morais et al (2008), the development of coffee tree berries passes through a series of distinct stages, whereby grain filling precedes ripening. According to these authors, the greencane coloring marks the beginning of ripening, when the berries begin to change from green to yellow, evolving until the cherry stage.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction of immature fruits removed from each batch of coffee can generally be differentiated into green and green-cane categories. Morais et al (2008) demonstrated, through a phenological scale, that the ripeness of coffee begins with green berries, which pass to green-cane and subsequently cherry. The green-cane stage, for being close to maturity, already presents characteristics which enable pulping.…”
Section: Introductionmentioning
confidence: 99%